The effect of feeding duration on omega fatty acid accumulation in muscle of village chicken fed diet supplemented with flaxseed oil - Idris, Lokman Hakim; Jamaludin, Farahiyah Ilyana; Mohammad, Mardhati; Abu Bakar, Nurulhayati; Ahmad, Hafandi; Samat, Noraini (Universiti Sultan Zainal Abidin, 2024)
Village chicken is an indigenous chicken which is known to have lean meat and now becoming one of the important protein sources available in Malaysia. The demand for this chicken has also increased in recent years as people has become more health conscious, and value-adding the meat product may be an advantage to improve its functional properties. Thus, an experiment was conducted to determine the optimum feeding duration of village chicken fed with diet supplemented with flaxseed oil on the accumulation of omega fatty acids in the breast and thigh muscles. A total of 120 male village chickens were randomly assigned to 4 treatments with 5 replications and were fed omega supplemented feed for 3 different duration lengths. The chickens were fed isonitrogenous and isocaloric corn-soy based diets supplemented with 2% flaxseed oil as omega source for 5 weeks (T5), 3 weeks (T3), 1 week (T1), and a control diet (T0) without any supplementation of flaxseed oil for 5 weeks. The omega fatty acids, linoleic acid (omega-6) and alpha-linolenic acid (omega-3) were present in all breast and thigh muscles except for control breast muscle. Chickens fed with flaxseed oil for 5 weeks showed highest accumulation of alpha-linolenic acid in thigh muscle (85.74mg/100g). Longer duration of feeding with flaxseed oil resulted with higher accumulation of alpha-linolenic acid in thigh muscle. In the breast muscle however, accumulation of alpha-linolenic acid was found to be abundant in the 3 weeks (42.12mg/100g) and 5 weeks (40.39mg/100g) treatment. The linoleic acid content in both thigh (360.22–440.95mg/100g) and breast (177.78–221.55mg/100g) muscles however were higher in all feeding durations compared to alpha-linolenic acid. In this study, it was found that 3 weeks of flaxseed oil supplementation is sufficient to accumulate the alpha-linolenic acid into the breast and 5 weeks supplementation for thigh muscle of village chicken.